Comparative Social and Economic Study of Youth Pro-Natalist Policy in the Regions of Germany, France and Russia - Gokova, Olga Vladimirovna; Kiseleva, Albina Musaevna (Economy of Regions, 2017)
This article analyzes the results of three empirical studies conducted in Russia, Germany and France, which reveal value orientations of contemporary young people of these countries, the nature of their social behavior in the demographic context, as well as economic factors influencing it. The objectives of the study are the need to identify and systematize the factors that influence the reproductive behavior of today’s youth from typical regions of these countries, as well as the evaluation of the experience of the organization and implementation of the pro-natalist policy accumulated by these three states. In the process of the questionnaire survey of young people in three countries, we formed an information database for the comparative analysis of young respondents’ views on the issues of identifying their behaviour and value orientations in family life. We also use materials of the state statistics of these countries and the secondary analysis of the materials of sociological studies. On the basis of the conducted research and experience of implementation of pro-natalist policy in Germany and France, we have developed a number of measures of the Russian youth pro-natalist policy. The development of the labor market has a strong influence on the formation of the family value system of today’s youth in Germany, France and Russia. It specifies the need to achieve a balance between creating a family, birth of children and the desire to create oneself as a professional. The possibility of achieving such life harmony must be ensured and supported by government measures in the framework of the effective pro-natalist policy.